Blood lactate, ammonia and kinematic indices during a speed-endurance training session in elite sprinters - Kantanista, Adam; Kusy, Krzysztof; Dopierała, Karolina; Trinschek, Jacek; Król, Hubert; Włodarczyk, Michał; Zieliński, Jacek (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. The analysis of both athletic performance and individual response to exercise helps control the training process. In order to fulfill these needs, various blood biomarkers, along with physiological and biomechanical parameters are tested using modern technology. Aim of Study. The aim of this study was to evaluate athletes’ response to the performed speed-endurance training session during the pre-competition phase. Material and Methods. The study sample comprised male sprinters competing in the 100 m, 200 and 4 × 100 m events at the national and international level. During training, blood samples were taken, which were analyzed regarding ammonia and lactate concentrations. Kinematic parameters were analyzed using the Catapult OptimEye S5 system. Results. In all athletes, maximum blood ammonia (176-181 μmol/l) and lactate concentrations (18.0-20.3 mmol/l) were observed three minutes after the last run during the main part of the training session. At the 30th minute of cool down, blood ammonia concentration was similar to the level before warm up, and lactate concentration was still increased. During the main part of the session, sprinters achieved maximum velocity 10.3-10.4 m/s. Conclusions. In highly-trained sprinters, a speed endurance training session causes a strong and prolonged exercise response, manifested by extremely high blood ammonia and lactate concentration as well as maximal heart rate. Kinematic indices help to individually optimize athletes’ exercise loads.
Keywords: sprinters; blood ammonia; lactate; speed endurance; monitoring training session